Epidemiological Profile of Fatal Poisoning Autopsy Cases Conducted at Gims, Kalaburagi, Karnataka- A Retrospective Study - Khaja Azizuddin Junaidi1 , Kashif Ali2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background- Pesticide poisoning is a major public health problem worldwide, with thousands of deaths occurring every year, mainly in developing countries. Its usage has been increased in recent past leading its misuse to commit suicide. The aim of this study was to determine the profile of fatal poisoning cases in and around Gulbarga district & to find out its correlates. Methodology- The present study is a retrospective study of fatal poisoning autopsy cases performed at GIMS, District Hospital, Kalaburagi, Karnataka from January 2018 to December 2018. During this period a total of 647 autopsy cases were conducted of which 85 cases were due to fatal poisoning. Relevant information and subjective data like age, sex, marital status, religion, seasonal variation, type of poison consumed and manner of death have been collected from medicolegal autopsy register, police inquest and treatment history using a predesigned proforma. Results- A total of 647 cases were autopsied during the year Jan 2018-Dec 2018. Out of 647 cases 85.9% cases were due to unnatural deaths of which 85 cases (13.1%) were due to suspected poisoning. In our study males outnumbered females with 67 cases (78.8%) compared to females with 18 cases (21.2%), maximum number of cases were in the age group between 21-30 years with 36 cases (42.4%). Maximum number of cases were from rural locality with 69 cases (81.2%) & majority of poisoning cases were seen during summer with 42 cases (49.4%). Maximum number of deaths were due to suicide (95.2%) followed by accidental poisoning (4.8%). Majority of poisoning cases were seen in Hindu population (82.3%) and maximum cases were seen in married people (74.1%). Conclusion- Agrochemical pesticides especially Organophosphorus compounds are responsible for most of the poison related fatalities, which is seen in our present study. Strict legal enforcement in selling and handling of agrochemicals is the need of the hour, and establishment of poison detection centres and early management of poisoning cases at all hospitals, primary health care centres could considerably minimise the morbidity and mortality due to poisoning.